Manajemen Sulit Jalan Napas pada Pasien Pediatrik dengan Sindrom Bosman-Arhinia Mikroftalmia - Mahmud; Widodo, Untung; Loru, Martha Yuanita (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
A 12-months-old boy with Bosman-Arhinia Microphthalmia Syndrome (BAMS) will undergo surgery to replace a nasopharyngeal duct catheter after nasal reconstruction. Patients with ASA physical status 2 with BAMS and prediction of difficult airway. Patient with a history of 2 months ago went on tracheostomy surgery, facilitated by general anesthesia using the Supraglotic Airway Device (SAD) or Laringeal Mask Airway (LMA). After 3 weeks, the tracheostomy cannula was removed and the tracheostomy wound was closed. We used crash induction but found difficulty in ventilation with a facemask or with the LMA so that management was immediately carried out according to the difficult airway algorithm and intubation was successful